(untitled) (Research, Society and Development, 2023)
Within the scope of pharmacists’ competence, prescription favors clinical efficacy in direct patient care, with the objective of contributing to the improvement of health care, providing safer and more efficient access to medicines, optimizing the use of the skills of health professionals. This literature review study, therefore, aimed to describe the importance of pharmaceutical prescription as a new clinical management tool, thus favoring the rational use of medicines. A literature review was carried out, including retrospective and prospective studies conducted in Brazil and abroad, which addressed pharmaceutical prescription and indiscriminate use of medicines. For this, an investigation was carried out in the MEDLINE, SciELO, LILACS and PUBMED databases, resulting in the selection of 10 studies. In view of the results found in the aforementioned studies, it is worth noting that pharmaceutical prescription, in addition to being supported by law (RDC 586/2013 - CFF), was a watershed in the pharmaceutical profession. Pharmacists are generally not familiarized with and prepared to exercise their clinical duties diligently. Pharmaceutical prescribing activities are regulated in several countries, however, they remain unknown to the majority of the population. This study points out some challenges involved in the practice of pharmaceutical prescription and its findings may be useful to suggest ways to strengthen the practice.